Hyperactivitypography from a to z. (Gestalten, 2010)
Who knew that a publication that looks like an attractively designed children's book could take such a revealing look at the demanding topic of typography. The colorful pages of hyperactivitypography from A to Z present a simple and fun, yet amazingly clever how-to that celebrates typography in all its complexity. Introducing common typography terms and trivia through charming illustrations, personal examinations and fun-filled exercises, this activity book offers both an accessible introduction to typography beginners and an entertaining review for experts to test their skills and take away new insights into the ramifications of typography--all while having fun.